The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.iecr.2c00934
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Wetting Properties of SiO2-Based Nanofluids to Create Durable Surfaces with Special Wettability for Self-Cleaning, Anti-Fouling, and Oil–Water Separation

Abstract: Surfaces with special wettability have aroused lots of attention due to their broad applications in many fields. In this work, we systematically report selective and various fabrications of nanofluids based on readily available materials such as SiO 2 nanoparticles and polydimethylsiloxane to create superhydrophobic, superoleophobic, superhydrophilic/superoleophobic, and underwater superoleophobic coatings. The efficiency of prepared coatings is investigated on mineral rock plates as porous substrates via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Multilayer polymer films and polymer coatings have become indispensable for the transport and storage of goods in many industries, offering a reliable, sanitary, and inexpensive solution to meet the demands of increasingly complex applications and environments. These films can have sophisticated structures that take advantage of the properties of individual polymer layers (e.g., puncture resistance, gas permeability, UV protection) to produce multilayer films optimized for specific applications. For example, a food storage film may include a Nylon or ethylene vinyl alcohol (EVOH) barrier layer in addition to a polyolefin layer providing a moisture or oxygen barrier, structural support, and sealability.…”
Section: Introductionmentioning
confidence: 99%
“…Multilayer polymer films and polymer coatings have become indispensable for the transport and storage of goods in many industries, offering a reliable, sanitary, and inexpensive solution to meet the demands of increasingly complex applications and environments. These films can have sophisticated structures that take advantage of the properties of individual polymer layers (e.g., puncture resistance, gas permeability, UV protection) to produce multilayer films optimized for specific applications. For example, a food storage film may include a Nylon or ethylene vinyl alcohol (EVOH) barrier layer in addition to a polyolefin layer providing a moisture or oxygen barrier, structural support, and sealability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Therefore, the fabrication of surfaces with unique dynamic omniphobicity has gained rapid momentum in the advancement of new materials. Interestingly, it has shown broad application prospects in a variety of elds, including selfcleaning, [6][7][8][9][10][11][12] anti-fouling, [10][11][12][13][14][15][16][17][18][19] anti-corrosion, 8,16-21 drag reduction 14,[21][22][23] and oil-water separation. 9,10,[24][25][26] Nepenthes is a representative dynamic omniphobic surface found in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has shown broad application prospects in a variety of elds, including selfcleaning, [6][7][8][9][10][11][12] anti-fouling, [10][11][12][13][14][15][16][17][18][19] anti-corrosion, 8,16-21 drag reduction 14,[21][22][23] and oil-water separation. 9,10,[24][25][26] Nepenthes is a representative dynamic omniphobic surface found in nature. Inspired by it, researchers have developed surfaces with dynamic omniphobicity that utilize a lubricantinfused structure.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, there are many examples of superhydrophobic surfaces possessing this special self-cleaning property such as butterfly wings, shark skin, and lotus leaves. It is revealed that this property of the lotus leaf or the “Lotus effect” results from the rough morphology and the hydrophobic epicuticular wax covering the entire surface leaf. Inspired by this discovery, many researchers have mimicked the “Lotus effect” by designing and fabricating artificial superhydrophobic surfaces using the combination of micro/nano or hierarchical morphologies and low surface energy materials. However, besides the elemental factors constituting the superhydrophobicity of a surface-like surface roughness and hydrophobic material coating, the superhydrophobic surface has to be transparent for applications requiring high optical transmittance like solar cell panel protection . Therefore, several strategies for fabricating flexible transparent superhydrophobic structures have been reported.…”
Section: Introductionmentioning
confidence: 99%